2011
DOI: 10.3109/02652048.2011.557746
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anin vitroreversible hypometabolism through chitosan-based nanoparticles

Abstract: The nanoparticulate drug delivery system described seems to be effective in inducing and prolonging a sort of hibernation-like state in the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…According to previous findings, 15 some chiNPs have been observed inside the cell nuclei. The size of the chiNPs used in both studies is incompatible with their passage through the nuclear pore complex; 22 , 23 moreover, chiNPs have never been found inside nuclei at short times after internalization.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…According to previous findings, 15 some chiNPs have been observed inside the cell nuclei. The size of the chiNPs used in both studies is incompatible with their passage through the nuclear pore complex; 22 , 23 moreover, chiNPs have never been found inside nuclei at short times after internalization.…”
Section: Discussionsupporting
confidence: 68%
“… 10 , 13-16 ChiNPs are therefore considered to be potentially good carriers for the sustained intracellular delivery of specific molecules, but scarce attention has been paid to the long-lasting permanence of these NPs in the intracellular milieu, as well as to their intracellular fate ( i.e ., distribution, interaction with cell organelles, and degradation) in the long (weeks) term. It has been previously demonstrated that chiNPs effectively enter human epithelial cells in culture 15 and gradually release the encapsulated drug into the intracellular milieu. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In B50 cells, as already observed in other cell types, chitosan NPs were never found inside the nucleus. Since nuclear localization of different NPs has been reported in other cell models in vitro , 12,3941 we can hypothesize that cell line characteristics, the chemical-physical features of NPs, or both may account for this finding. It seems therefore important to test the nuclear accessibility for each cell line as well as for NP characteristics.…”
Section: Discussionmentioning
confidence: 55%
“…912 Chitosan-based NPs enter the cells by various endocytic processes, which may vary in different cell types and have not been fully identified: their uptake appears to occur predominantly by adsorptive endocytosis, but also clathrin- and caveolin-mediated pathways as well as clathrin- and caveolin-independent endocytosis may be involved. 1319 …”
Section: Introductionmentioning
confidence: 99%